Clinic Building - Nimpuno, Krisno (Self published, 1980)
The objective of constructing low cost health buildings is not simply to build cheaply, but rather to construct fully adequate facilities for the lowest possible cost; or, in other words, to achieve a maximum health care capacity from each invested dollar. This may seem to be a very superficial remark, but there are in reality staggering differences in costs between hospitals of equal capacity within almost each of the LDCs, which give us ample reason for questioning the present practice. Does anyone really, helieve that ,medical €are .is ten times more effective in a ten times costlier hospital bed? Does anybody believe that a reasonable hospital bed/population ratio can be achieved with high rise, air conditioned hospitals in countries with a GNP/Capital of less than $500:- per annum? The answer is naturally no. Nobody believes that. But why do governments and technical assistance agencies build such costly facilities? The answer is that the elites taking those decisions are not sincere in their proclaimed efforts to provide equal care for the whole nation.
Clinic Building Research in Kenya
Research Report
Keywords: Clinic Building, Kenya